2011
DOI: 10.1016/j.acap.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Children’s Health Care Quality Measures for Medicaid and CHIP: An Evidence-Informed, Publicly Transparent Expert Process

Abstract: An open national public process combined with an evidence-informed evaluation methodology resulted in identification of a balanced, grounded, and parsimonious core set of measures that should become feasible to implement on a widespread scale over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 7 publications
0
57
0
Order By: Relevance
“…Managed care organizations are interested in immunization and preventive care visit rates, which are Healthcare Effectiveness Data and Information Set (HEDIS) quality measures. [33][34][35][36][37] However, managed care organizations may not have accurate family contact information and families may not respond to reminders emanating from managed care plans.…”
Section: Introductionmentioning
confidence: 99%
“…Managed care organizations are interested in immunization and preventive care visit rates, which are Healthcare Effectiveness Data and Information Set (HEDIS) quality measures. [33][34][35][36][37] However, managed care organizations may not have accurate family contact information and families may not respond to reminders emanating from managed care plans.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Content gaps led to recommendations for new measures for substance abuse care and mental health treatment as well as in several areas relevant to child mental health: specialty care, inpatient care, availability of services, coordination of care, medical home, family experiences of care, and outcomes. 27,31,34,35 Furthermore, the SNAC strongly encouraged new quality measures to be aligned with the priorities of state Medicaid and CHIP agencies, 36,37 providers, and parents. 38,39 …”
Section: Chipra: Development Of Initial Core Set Of Measuresmentioning
confidence: 99%
“…Details of the methods and administrative review pathways before final submission of the initial core set of measures are described elsewhere. 27,28,31 In addition to selecting measures, the SNAC provided guidance to the Pediatric Quality Measures Program. It found that measures lacked the capacity to stratify adherence according to race/ethnicity, tribe, socioeconomic state, or special health care need status, characteristics called for in the CHIPRA legislation.…”
Section: Chipra: Development Of Initial Core Set Of Measuresmentioning
confidence: 99%
See 2 more Smart Citations